Advanced F-Transform-Based Image Fusion. (4th October 2012) - Vajgl, Marek; Perfilieva, Irina; Hod'áková, Petra
Abstract : We propose to use the modern technique of the F-transform in order to show that it can be successfully applied to the image fusion. We remind two working algorithms (SA—the simple algorithm, and CA—the complete algorithm) which are based on the F-transform and discuss, how they can be improved. We propose a new algorithm (ESA—the enhanced simple algorithm) which is effective in time and free of frequently encountered shortcomings.